2017
DOI: 10.5194/acp-17-11041-2017
|View full text |Cite
|
Sign up to set email alerts
|

Pre-monsoon air quality over Lumbini, a world heritage site along the Himalayan foothills

Abstract: Abstract. Lumbini, in southern Nepal, is a UNESCO world heritage site of universal value as the birthplace of Buddha. Poor air quality in Lumbini and surrounding regions is a great concern for public health as well as for preservation, protection and promotion of Buddhist heritage and culture. We present here results from measurements of ambient concentrations of key air pollutants (PM, BC, CO, O 3 ) in Lumbini, first of its kind for Lumbini, conducted during an intensive measurement period of 3 months (April-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 79 publications
5
43
0
Order By: Relevance
“…However, recently, both of the sites have gained popularity as one of the polluted regions in south Asia. More on these sites have already been explained elsewhere (Rupakheti et al, 2017;Rupakheti et al, 2018;Tripathee et al, 2017). Figure 1.…”
Section: Study Sitessupporting
confidence: 54%
See 1 more Smart Citation
“…However, recently, both of the sites have gained popularity as one of the polluted regions in south Asia. More on these sites have already been explained elsewhere (Rupakheti et al, 2017;Rupakheti et al, 2018;Tripathee et al, 2017). Figure 1.…”
Section: Study Sitessupporting
confidence: 54%
“…However, over both sites, aerosol types were identified as those from anthropogenic activities, biomass burning and mixed (undetermined) in high frequency. During the pre-monsoon and post-monsoon seasons, IGP also experiences extensive forest fire and agro-residue burning (Habib et al, 2006;Ram and Sarin, 2011;Rupakheti et al, 2017) which impacts the distant locations even across the Himalayas in the Tibetan Plateau too (Cong et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have indicated the likelihood of regional longrange transport contributing to air pollution in different parts of Nepal (Marinoni et al, 2013;Tripathee et al, 2014;Dhungel et al, 2018;Rupakheti et al, 2017;Lüthi et al, 2015;Wan et al, 2017, including the Kathmandu Valley, especially during the premonsoon period (Panday and Prinn, 2009;Putero et al, 2015;Bhardwaj et al, 2018). During the premonsoon season, frequent agro-residue burning and forest fires are reported in the IGP region, including southern Nepal and the Himalayan foothills in India and Nepal (Ram and Sarin, 2010;Vadrevu et al, 2012), as well as in the Kathmandu Valley.…”
Section: Regional Influence On Co In the Valleymentioning
confidence: 99%
“…Until recently the emissions, types, levels, atmospheric transport and transformation, impacts, and mitigation of various atmospheric pollutants were not well characterized in the vast mountain areas and the foothill region in South Asia. In this context, the international project of "A Sustainable Atmosphere for the Kathmandu Valley (SusKat)" was launched, aiming to comprehensively understand the causes of the severe air pollution in the region, and identifying appropriate solutions to reduce its impacts (Rupakheti et al, 2019). This paper presents analyses of samples collected as part of the SusKat field campaign.…”
Section: Introductionmentioning
confidence: 99%